Comparative Efficacy and Reinfection of Albendazole-mebendazole, Albendazole-pyrantel Pamoate, and Mebendazole on Soil-transmitted Helminths - Husin, Nirmalia; Pasaribu, Ayodhia Pitaloka; Ali, Muhammad; Suteno, Erwin; Wijaya, Wilhans; Pasaribu, Syahril (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Soil-transmitted helminths (STHs) infection (i.e., Ascaris lumbricoides, Trichuris trichiura, and hookworm) are commonly found as a single infection as well as a mixture of the three kinds of helminths that requires a broad anthelmintic spectrum. Some study revealed that combination of anthelmintic provides better efficacy. AIM: The objective of the study was to compare the efficacy of combination treatment of albendazole-mebendazole, albendazole-pyrantel pamoate, and mebendazole alone in treating STHs infection as well as the rate of reinfection post-treatment. METHODS: In 2018, a randomized controlled trial was conducted in Batubara district, North Sumatera. School-aged children diagnosed for STH were randomly allocated to (1) albendazole-mebendazole; (2) albendazole-pyrantel pamoate; or (3) mebendazole treatment groups. Here, we report the efficacy (cure rates [CRs] and egg-reduction rates [ERR]) and reinfection rates determined 12 weeks post-treatment. Chi-square test was used to compare the drug efficacy and reinfection rate between three groups. RESULTS: A total of 309 children complete baseline and follow-up data. The efficacy was determined after 4 weeks post-treatment albendazole-pyrantel pamoate showed a significant higher efficacy against A. lumbricoides (CR: 93.5%; ERR: 100%) and T. trichiura (CR: 81.4%; ERR: 99%). For hookworm infection, results showed higher efficacy between the three groups after treatment. The reinfection rates 12 weeks after treatment for A. lumbricoides infection (Group 1: 3.1%; 2: 3%; 3: 1.3%) with p > 0.05 and for T. trichiura infection (Group 1: 19.2%; 2: 25%; 3: 1.5%) with p < 0.05. CONCLUSION: This study showed the excellent efficacy of an albendazole-pyrantel pamoate combination against STHs infections. The highest reinfection rate was found in albendazole-pyrantel pamoate group for T. trichiura infection.